ENHANCING MEDICAL EDUCATION THROUGH VIRTUAL REALITY: INNOVATIVE METHODS AND PRACTICES - Rustamov Mirodiljon Muhammadjanovich (Лучшие интеллектуальные исследования, 2024)
Abstract: In recent years, Virtual Reality (VR) technologies have emerged as promising tools in medical education, offering immersive and interactive experiences that enhance learning outcomes. This article explores the various methods and applications of VR in medical education, highlighting its potential to revolutionize traditional teaching approaches. Through a comprehensive review of existing literature and case studies, we delve into the effectiveness of VR in simulating clinical scenarios, anatomical exploration, procedural training, and collaborative learning environments. Furthermore, we discuss the challenges and future directions of integrating VR into medical curricula, emphasizing the importance of evidence-based practices and continuous innovation to optimize learning experiences for future healthcare professionals.